MASALAH PERPAJAKAN DALAM BEBERAPA PRASASTI BALI KUNO - I Nyoman Sunarya (BRIN, 1994)
Inscription as a heritage from the past is one of the data used as material for analysis in the context of the reconstruction of human life. Balinese inscriptions from the oldest times until the inscriptions published later, mentioned several terms related to taxation. Based on data recorded in several ancient Balinese inscriptions, ancient Balinese people had experienced tax problems. The appearance of the king as a mediator in anticipating the problems faced by the community proves that they really paid attention to the peace and welfare of their people.